Review of the book by Janusz Mariański, entitled The sense of life – the value – the religion. Sociological study Published by KUL, Lublin 2013 - Kościołek, Aneta (Nursing in the 21st Century, 2013)
REVIEW OF THE BOOK BY JANUSZ MARIAŃSKI, ENTITLED THE SENSE OF LIFE – THE VALUE – THE RELIGION. SOCIOLOGICAL STUDY PUBLISHED BY KUL, LUBLIN 2013Questions: “who is the man, where does he/she aim, what should he/she do, what values does he/she prefer in his/her worldly life, what is the sense and meaning of his/her life and death as well as dying“, are the most difficult questions of not only human existence, but also whole universe. Janusz Mariański by comparing the results of many investigations seeks the psychological- social conditioning of the sense of life as well as is wondering if the contemporary Polish youth strives to understand the sense and the aim of life, what values are they guided by and what place in their life does the religion occupy.